AJHP: Redesigned - Jill A. Sellers (American Journal of Health-System Pharmacy, 2000)
PURPOSE: Development and implementation of an emergency department protocol for use of subcutaneous (SQ) insulin in patients with mild to moderate diabetic ketoacidosis (DKA) is described. SUMMARY: Diabetes is on the rise worldwide in what has been described as a coming tsunami, with proportional increases in DKA, outstripping the availability of intensive care unit (ICU) and intermediate care unit beds. Historically, the complexity of care for DKA and safety concerns restricting use of intravenous insulin infusion on medical floors have required admission to an ICU. A potential solution to these concerns is in use of subcutaneous insulin for treating DKA, which avoids an insulin infusion and the intensity of monitoring that requires nursing staff ratios only available in the ICU. Recently our multidisciplinary team implemented a protocol for use of subcutaneous (SQ) insulin in patients with mild- to moderate-severity DKA presenting to the emergency department (ED) called the SQuID (Subcutaneous Insulin in Diabetic Ketoacidosis) protocol. This was followed with a second study expanding the locations to which these patients can be admitted. We are currently expanding this protocol in some of our community affiliate hospitals. Now in its fourth year, this protocol has been highly successful, with over 75% of patients with mild to moderate DKA (nearly all who are eligible) being treated on SQuID and resulting in a more than 33% reduction in ICU utilization for this population. CONCLUSION: Implementation of the SQuiD protocol along with comprehensive education, ongoing monitoring, and targeted modifications to reduce hypoglycemia risk has advanced our institution's efforts to provide a safe alternative to conventional DKA management.